2005
DOI: 10.1152/jn.00132.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Path Integration Versus Environmental Orientation on Place Cell Remapping Between Visually Identical Environments

Abstract: To assess the effects of interactions between angular path integration and visual landmarks on the firing of hippocampal neurons, we recorded from CA1 pyramidal cells as rats foraged in two identical boxes with polarizing internal cues. In the same-orientation condition, following an earlier experiment by Skaggs and McNaughton, the boxes were oriented identically and connected by a corridor. In the opposite-orientation condition, the boxes were abutted by rotating them 90 degrees in opposite directions, so tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
77
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(100 citation statements)
references
References 41 publications
14
77
1
Order By: Relevance
“…With respect to place cell processing, one key methodological difference that could explain these differences is the fact that testing in the Mizumori study involved navigation in the radial arm maze, which may require greater reliance on directional orientation to disambiguate the different arm locations. Some recent work by Greives et al (2016) supports this view in showing that place cells tend to express similar firing fields in environments that are arranged in parallel, i.e., in the same direction, but show unique firing fields in environments that are radially arranged, i.e., have different directional orientations (see also Fuhs et al, 2005;Spiers et al, 2015). Whether directional inputs from the anterior thalamus influence the establishment of unique place fields in identical, radially arranged, compartments is presently unclear, but would be consistent with the loss of head direction cell activity in major hippocampal input regions (Goodridge & Taube, 1997;Winter et al, 2015), and the reported loss of directional navigation after anterior thalamus inactivation (Stackman et al, 2012).…”
Section: Summary Conclusion and Unanswered Questionsmentioning
confidence: 90%
“…With respect to place cell processing, one key methodological difference that could explain these differences is the fact that testing in the Mizumori study involved navigation in the radial arm maze, which may require greater reliance on directional orientation to disambiguate the different arm locations. Some recent work by Greives et al (2016) supports this view in showing that place cells tend to express similar firing fields in environments that are arranged in parallel, i.e., in the same direction, but show unique firing fields in environments that are radially arranged, i.e., have different directional orientations (see also Fuhs et al, 2005;Spiers et al, 2015). Whether directional inputs from the anterior thalamus influence the establishment of unique place fields in identical, radially arranged, compartments is presently unclear, but would be consistent with the loss of head direction cell activity in major hippocampal input regions (Goodridge & Taube, 1997;Winter et al, 2015), and the reported loss of directional navigation after anterior thalamus inactivation (Stackman et al, 2012).…”
Section: Summary Conclusion and Unanswered Questionsmentioning
confidence: 90%
“…The question of how unified the interaction between place cells is has been a contentious one over the years (McNaughton et al, 1994;Samsonovich and McNaughton, 1997;Redish et al, 1998;Redish, 1999;Harris et al, 2003;Harris, 2005;Touretzky and Muller, 2006) with data supporting both the idea that cells respond individually (Anderson and Jeffery, 2003;Tanila et al, 1997;Lee et al, 2004) and other data supporting changes occurring in the map as a whole (O'Keefe and Conway, 1978;Markus et al, 1995;Barnes et al, 1997;Leutgeb et al, 2005Leutgeb et al, , 2007 as well as data suggesting partial remapping (Quirk et al, 1990;Skaggs and McNaughton, 1998;Knierim, 2002;Leutgeb et al, 2004;Vazdarjanova and Guzowski, 2004;Lee et al, 2004;Fuhs et al, 2005). Similarly, place cell responses to subgoals within a task (Eichenbaum et al, 1987;Wiener et al, 1989;Cohen and Eichenbaum, 1993;Hampson et al, 1993;Wood et al, 2000;Ferbinteanu and Shapiro, 2003) have been proposed to arise from goal-dependent submaps (Touretzky and Redish, 1996;Redish and Touretzky, 1997;Redish, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This includes sensitivity to proximal and distal landmarks (Siegel et al 2008;Yoganarasimha et al 2006;Renaudineau et al 2007), contextual cues (including nonspatial ones like color and lighting) (Muller and Kubie 1987;Hampson et al 1999;Wood et al 1999Wood et al , 2000Hayman et al 2003;Komorowski et al 2009;Manns and Eichenbaum 2009), geometric boundaries (Lever et al 2002), and reward associations (Wikenheiser and Redish 2011). Place cells continue to fire in the absence of visual cues, suggesting that their activities can be updated through idiothetic cues (Fuhs et al 2005;Gothard et al 1996;Knierim et al 1996;Taube et al 1996;Jeffery et al 1997;Quirk et al 1990). These results support the hypothesis by O'Keefe and Nadel that the hippocampus contains the brain's spatial map and that this map derives from both idiothetic and allothetic cues.…”
Section: Place Cellsmentioning
confidence: 99%